Undang-Undang Pajak Perseroan, Pajak Pendapatan, PBDR, dan MPS-MPO sebagaimana berlaku sekarang (Yayasan Bina Pajak, 1981)
Tax laws for commercial firms, income, interest, dividends, and royalties; with changes made in former Dutch tax laws.